2020
DOI: 10.1109/access.2020.3013282
|View full text |Cite
|
Sign up to set email alerts
|

EC-ElGamal and Genetic Algorithm-Based Enhancement for Lightweight Scalable Blockchain in IoT Domain

Abstract: Security, data privacy and decentralization are significant challenges in the Internet of Things (IoT) domain. These challenges are inherited attribute of another emerging technology, Blockchain. This enforced convergence of IoT and Blockchain, attracting researchers to study on the effective use of Blockchain's strength to solve the challenges of IoT. Rapid IoT adoption requires standardization and mature solution on security, data protection for compliance and performance for commercialization. These demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Gene inversions can be classified as single or multiple inversions. Single-point inversions are performed by inverting only one substring of a chromosome, while multipoint inversions are performed by inverting j substrings of a chromosome with a random number j(1 ≤ j ≤ u) for a pre-given positive integer u [21][22][23].…”
Section: Gene Inversion Operatormentioning
confidence: 99%
“…Gene inversions can be classified as single or multiple inversions. Single-point inversions are performed by inverting only one substring of a chromosome, while multipoint inversions are performed by inverting j substrings of a chromosome with a random number j(1 ≤ j ≤ u) for a pre-given positive integer u [21][22][23].…”
Section: Gene Inversion Operatormentioning
confidence: 99%
“…In this section, we review some of the methods for finding the problem formulation of the blockchain technology required for developing efficient security enhancement. Guruprakash and Koppu (2020) Guo et al (2021) introduced efficient traceable attribute-based encryption with dynamic access control (TABE-DAC). Blockchains are also used to integrate access control and distributed storage for the sharing of personal information.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that application of ECC significantly help to improve the overall performance. Healthcare Storage optimisation, Efficiency improvement, Access control, Authentication, Security enhancement, Privacy, Identity management [22], [23], [28], [36], [37] IoT Mobile Privacy, Authentication, Key generation, Privacy-preserving, Security enhancement [35], [26] Security Enhancement Enhance security, Runtime optimisation [42], [72] ECDSA Cloud Cloud storage Performance improvement, Security enhancement, Storage, Signature , Privacy, Data management [27], [33], [41], [31] Cryptocurrency Signature generation verification, Provability, Privacy, Enhanced security, Identity Key management [29], [34], [38], [40], [24] Electric vehicle Storage, Security enhancement, Privacy, protection [37], [25], [39] Table 3: Application of ECC in blockchain.…”
Section: Application Of Elliptic Curve Cryptography In Blockchainmentioning
confidence: 99%
“…As presented in Figure 5 on page 284, the Edwards curve security level is far stronger at all security levels of 128,192 and 256 compared with the Weierstrass curve. Security level comparison of rho complexity is derived from [71] and [72].…”
Section: Security Comparisonmentioning
confidence: 99%